(untitled) (Research, Society and Development, 2022)
Gynecological emergencies are common, and ovarian torsion is the main situation encountered. Its consequences can range from acute unilateral pelvic pain to female infertility, and in order to avoid this, the most reliable studies possible are needed. Thus, the aim was to evaluate the techniques used in ovarian ischemia in rats. From this, an analysis of the most used methods, biochemical and histopathological analyzes was made, so that a comparison could be established with those that may be more efficient in carrying out studies to alleviate the problems caused by ovarian torsion. A search was carried out on the Pubmed, Scielo and Lilacs platforms, from 2017 to 2022, with the descriptors “ovarian torsion”, “Reperfusion injury” and “rats”, and 50 articles were selected. The results were that 62% of the articles used a vascular clamp, the main biochemical marker was malondialdehyde in 70%, and the histopathological markers were related to tissue integrity, such as follicular degeneration, edema, leukocyte infiltration and vascular congestion. Thus, it can be inferred that they are the most effective methods to simulate ovarian ischemia.